Queer indigenous studies: Critical interventions in theory, politics, and literature - Driskill, Qwo-Li; Finley, Chris; Gilley, Brian Joseph; Morgensen, Scott Lauria (The University of Arizona Press, 2011)
"Ce livre est une imagination." Ainsi commence cette collection examinant les approches critiques centrées sur les Autochtones pour comprendre la vie et les communautés gaies, lesbiennes, bisexuelles, transgenres, queer et bispirituelles (GLBTQ2) et les implications créatives de la théorie queer dans les études autochtones. Ce livre n’est pas tant un manifeste qu’un dialogue – une « écriture dans une conversation » – entre un groupe lumineux d’universitaires-activistes revisitant l’histoire des études gaies et lesbiennes dans les communautés autochtones tout en ouvrant la voie à des théories et méthodologies centrées sur les Autochtones. L’ouverture audacieuse aux études autochtones queer invite à de nouveaux dialogues dans les études autochtones sur les orientations et les implications des études autochtones queer. La collection engage notamment les mouvements autochtones GLBTQ2 comme des alliances qui appellent également des allié.e.s au-delà de leurs frontières, que les coéditeurices et contributeurices modèlent en croisant leurs identités variées, notamment autochtone, trans, hétérosexuelle, non-autochtone, féministe, bispirituelle, mixte. du sang et des homosexuels, pour n'en nommer que quelques-uns. Enraciné.e.s dans les Amériques autochtones et le Pacifique, et s’appuyant sur des disciplines allant de la littérature à l’anthropologie, les contributeurices de Queer Indigenous Studies appellent les mouvements autochtones GLBTQ2 et leurs allié.e.s à centrer une analyse qui critique la relation entre le colonialisme et l’hétéropatriarcat. En répondant aux tournants critiques de la recherche autochtone qui centrent les épistémologies et les méthodologies autochtones, les contributeurices se joignent à la refonte des études autochtones, des études queer, des études transgenres et des féminismes autochtones. Basé sur la réalité selon laquelle les peuples autochtones queer « subissent une oppression à plusieurs niveaux qui a un impact profond sur notre sécurité, notre santé et notre survie », ce livre est à la fois une imagination et une invitation au/la lecteurice à se joindre à la discussion sur la décolonisation de la recherche, de la théorie et de la théorie des peuples queer autochtones. , ce faisant, de participer à la résistance alliée œuvrant en faveur d’un changement positif.
Keywords: approches et analyses; corps; histoire et politique; hétérosexisme; identités LGBTQIA2+; patriarcat; queer; racisme; système colonial; systèmes d'oppressions; thématiques; violences

The Intersex Enchiridion: Naming and Knowledge - Holmes, Morgan (Somatechnics, 2011)
The 2006 Lawson Wilkins Pediatric Endocrinology Society (LWPES) consensus to alter clinical language from ‘intersex’ to Disorders of Sex Development (DSD) has not met its stated objective of destigmatizing the ‘intersex’ label. Rather, DSD works to paper over a problematic understanding of morphological variation as disease. This article interrogates the development of DSD terminology in the clinical context of treating intersex and argues that ‘DSD’ reinstitutionalises clinical power to delineate and silence those marked by the diagnosis; that this silencing is precisely the point of the new terminology; and that it is against that retrenchant impulse that we must protect the viability of ‘intersex’ by continuing its critical deployment. This paper is based on an application of embodiment studies models of critique, combined with an orientation grounded in queer theory to critically interrogate the development of both DSD language and of the ‘new’ guidelines for clinical use, and of the Handbook for Parents that were developed out of the 2006 LWPES meetings. Some of my critique is based on work done over an 18-year period with adults who created the contemporary intersex movement, and on my previous research (in particular: Holmes 2002, 2008, 2010). The point of the argument is not to determine which diagnostic language is superior, but to retain the hard-won right to secure for ourselves the ability to operate socially without the stamp of ‘disorder’ or ‘disease’ strictly delineating what counts as ‘truth’ with regard to embodiment. In this sense, the argument applies to and is drawn out of a larger disability scholarship and activism framework that refuses to permit medicine the final voice in defining our bodies and our selves. The title refers to an older handbook, the enchiridion as a gesture toward the need to retain fundamental knowledge of self that intersexed persons can trace back to a more flexible understanding of embodied differences than the language of disorder asserts in the new Handbook for Parents.
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amérique du nord; amériques; approches et analyses; corps; cours; discipline; identité; intersexuation; militance; personnes intersexes; premier cycle; périodes historiques; queer; régions géographiques; santé; sciences humaines; soc2014; sociologie; thématiques; violences; violences médicales; états-unis

Law Reform, Lesbian Parenting, and the Reflective Claim - Leckey, Robert (Social & Legal Studies, 2011)
The article aims to complicate efforts to make law fit or catch up to social practices. It scrutinizes the ‘reflective claim’ using the case study of recognition of parenting by lesbian couples. Reforms in the United Kingdom’s Human Embryology and Fertilisation Act 2008 and the Canadian province of Quebec’s civil code are compared with empirical work from the social sciences on lesbians’ family practices. The reflective claim rests on problematic ideas about social practices and law. Since law is always blunt and incomplete, choices must be made as to which practices it should aim to recognize. Furthermore, the impact of heterosexist and homophobic conditions on lesbian families means that observable practices may not be a suitable model for gay-affirmative reforms. As advanced in the literature, the reflective claim overlooks law and society’s complex interaction, including how reform will not merely reflect but also alter practices. It fails to do justice to law reform’s normative character, obscuring its costs and positive potential
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amérique du nord; amériques; angleterre; approches et analyses; canada; corps; cours; discipline; discours dominant; droit; droit des femmes*; europe; hétérosexisme; identités LGBTQIA2+; inégalités; maternité; parentalité; premier cycle; périodes historiques; queer; québec; régions géographiques; science politique et droit; sciences humaines; soc2264; sociologie; systèmes d'oppressions; thématiques

Changing the framework: Disability justice - Mingus, Mia (Leaving Evidence, 2011)
Pendant mon travail de justice sociale, j'ai découvert que le handicap est quelque chose que la plupart des gens connaissent très peu - et cela inclut des organisateurs et des militants communautaires chevronnés, féroces et très respectés. Les gens considèrent généralement le handicap comme un défaut ou un problème individuel, plutôt que comme quelque chose en partie créé par le monde dans lequel nous vivons. Il est rare que les gens pensent au handicap comme une expérience politique ou comme englobant une communauté pleine d'histoires, de cultures et d'héritages riches. .
Keywords: approches et analyses; capacitisme; corps; cours; discours dominant; fem3300; identités LGBTQIA2+; inégalités; justice sociale; personnes handicapé.e.s*; premier cycle; queer; ressource en ligne; systèmes d'oppressions; thématiques

Moving toward the ugly: A politic beyond desirability - Mingus, Mia (Leaving Evidence, 2011)
*Femmes Of Color Symposium Keynote Speech, Oakland, CA (8/21/11)
Keywords: approches et analyses; capacitisme; corps; cours; discours dominant; fem3100; identités LGBTQIA2+; premier cycle; privilèges; queer; racisme; ressource en ligne; sexisme; sexualité; systèmes d'oppressions; thématiques